Intellectual Property Law in Malaysia - Tay, Pek San, author 300573 (Subang Jaya, Selangor : Thomson Reuters Asia Sdn Bhd, 2020)
This book is a detailed work that gives a distinctively Malaysian account of the six areas of law that are conventionally accepted as falling under the rubric of intellectual property: the law of passing off, registered trademarks, copyright, patents, registered industrial designs and confidential information. It provides a basic but comprehensive account of the substantive rules that govern these areas of intellectual property law, with the focus being essentially on the Malaysian position. In treating intellectual property law as a coherent whole, this book enables the inter-relationship and the similarities that exist between the different areas to be better appreciated. In addition to the thorough survey of local law, references have been made to case law from foreign jurisdictions where uncertainties arise in the local position. This provides a different perspective on possible approaches that may be applicable in addressing the local issues. In the areas which are governed by statutes, an outline of the historical background, justifications for protection and the international influences that have shaped those areas are provided so as to convey a better understanding of the nature of the law of intellectual property. Written by an experienced teacher and researcher of intellectual property law, this book provides clear analysis and discussion of the law, supported by copious citation of authorities. This new edition is fully up to date, taking into account new case law and statutory developments.